Diet alters delayed selfing, inbreeding depression, and reproductive senescence in a freshwater snail. Issue 14 (22nd June 2014) - Auld, Josh R.; Henkel, John F.
Abstract Reproductive success is a critical fitness attribute that is directly influenced by resource availability. Here, we investigate the effects of diet‐based resource availability on three interrelated aspects of reproductive success: a change in mating system based on mate availability, consequent inbreeding depression, and the deterioration of reproductive efficiency with age (senescence). We employed a factorial experimental design using 22 full‐sib families of the hermaphroditic freshwater snail Physa acuta to explore these interactions. Individual snails were reared in one of two mate‐availability treatments (isolated [selfing] or occasionally paired [outcrossing]) and one of two diet treatments (boiled lettuce or Spirulina, an algae that is rich in protein, vitamins, and minerals). Spirulina‐fed snails initiated reproduction at a 13% earlier age and 7% larger size than lettuce‐fed snails. Spirulina also resulted in a 30% reduction in the time delay before selfing. Compared to lettuce, a diet of Spirulina increased inbreeding depression by 52% for egg hatching rate and 64% for posthatching juvenile survival. Furthermore, Spirulina led to a 15‐fold increase in the rate of reproductive senescence compared with a diet of lettuce. These transgenerational, interactive effects of diet on inbreeding depression and reproductive senescence are discussed in the context of diet‐induced phenotypic plasticity.